Evaluation of mechanical, thermal, electrical, and transport properties of MWCNT‐filled NR/NBR blend composites. Issue 6 (3rd July 2017) - Thomas, Saliney; George, Soney C.; Thomas, Sabu
Abstract : Carbon nanotube based polymer nanocomposites found versatile applications and hence studying its reinforcing effect on NR/NBR blend system is a promising step in developing flexible elastomer gadgets. In this study, attempts have been made to prepare multi‐walled carbon nanotube (MWCNT)‐filled nanocomposites of NR/NBR blends. Raman spectra and transmission electron microscopic analysis indicate that there has been a finer and uniform dispersion of carbon nanotubes within the polymer matrix. Mechanical properties like tensile strength, tear resistance, abrasion loss and compression set of pure and blend samples showed an improvement with the increase in the dosage of MWCNT from 0.5 to 4 phr. 70/30 NR/NBR blend with 4 phr of MWCNT showed an improvement of 83% in tensile strength and 72% in tear strength compared to pure NBR. This is attributed to the uniform dispersion, high surface area, nano level interaction, and compatibility of MWCNT with the polymeric molecular chains. MWCNT is acting as a compatibilizing agent as is manifest from the increased negative values of free energy. Electrical conduction and thermal stability of the mixes were increased with the concentration of MWCNT due to the increase in the interfacial interaction resulting from the pi‐pi interaction with the nanotubes. POLYM. ENG. SCI., 58:961–972, 2018. © 2017 Society of Plastics Engineers